2020
DOI: 10.1002/jez.2404
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to prenatal PCBs shifts the timing of neurogenesis in the hypothalamus of developing rats

Abstract: The developing brain is highly sensitive to the hormonal milieu, with gonadal steroid hormones involved in neurogenesis, neural survival, and brain organization. Limited available evidence suggests that endocrine‐disrupting chemicals (EDCs) may perturb these developmental processes. In this study, we tested the hypothesis that prenatal exposure to a mixture of polychlorinated biphenyls (PCBs), Aroclor 1221, would disrupt the normal timing of neurogenesis in two hypothalamic regions: the ventromedial nucleus (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…Buijs et al (1980) reported that vasopressin content in the brain of developing rats increased beginning on E16, and that oxytocin content decreased from E16 to E18 but increased thereafter. It is also notable that neurogenesis in the hypothalamus of rodents occurs from mid to late gestation (Cheung et al, 2013;Hernandez Scudder et al, 2020a;Shimada & Nakamura, 1973). Therefore, our exposure window overlaps several key neurodevelopmental events involved in the generation and organization of hypothalamic neural circuits, including those involved in the control of social behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…Buijs et al (1980) reported that vasopressin content in the brain of developing rats increased beginning on E16, and that oxytocin content decreased from E16 to E18 but increased thereafter. It is also notable that neurogenesis in the hypothalamus of rodents occurs from mid to late gestation (Cheung et al, 2013;Hernandez Scudder et al, 2020a;Shimada & Nakamura, 1973). Therefore, our exposure window overlaps several key neurodevelopmental events involved in the generation and organization of hypothalamic neural circuits, including those involved in the control of social behaviors.…”
Section: Discussionmentioning
confidence: 97%